ANALYSIS OF THEORETICAL VIEWS ON THE MODERN USE OF LINGUISTIC AND CULTURAL IDIOMS (Proceedings of International Conference on Educational Discoveries and Humanities, 2024)
Idioms comprise the primary and the most significant type of phrasemes. Although there are many conflicting definitions for the term “idiom”, all attempts to define the notion can be boiled down to two fundamental approaches: either an idiom is defined using very general statements about its expressive and image-bearing functions or it is defined using a system of strict oppositions (Mel'cuk,1960). A brief outline of the idiomaticity theory was presented, among other things, in Baranov and Dobrovolski books (2005,2008). However, there are still issues to understand theoretical views of contemporary phraseological units clearly and deeply. Considering problems like these, this paper aims to illustrate analysis of theoretical views people may encounter with while studying phraseological expressions and introduces some ways to comprehend their idiomatic nature concerning with national-cultural identities in the modern usage of idioms.